Nonmyeloablative pentostatin-cyclophosphamide preconditioning improves rates of engraftment in adults undergoing haploidentical HCT for sickle cell disease - Emily Limerick; Matthew Hsieh; Jackie Queen; Mary Lacy Grecco; Julia Varga; Jennifer Brooks; Wynona Coles; Neal Jeffries; Courtney D. Fitzhugh (PLoS ONE, 2026)
The morbidity and mortality of sickle cell disease (SCD) remain high. Novel nonmyeloablative haploidentical hematopoietic cell transplant (HCT) regimens are being proposed. Methods This report compared the effect of adding an IV pentostatin and oral cyclophosphamide (PC) preconditioning to the nonmyeloablative NIH HCT platform of alemtuzumab and total body irradiation (TBI) in adults with severe SCD. Transplant outcomes were compared to a historical HCT cohort that did not receive the PC preconditioning. Results Thirty-nine adult SCD patients were included. The median age was 33 years, 61% were male, and 92% were HbSS genotype. The median follow-up was 6.5 years. Many patients had severe end-organ damage, including dialysis-dependent end-stage kidney disease (8%) and cirrhosis (10%). One-year overall survival was 95%. The PC regimen was associated with a reduction in acute rejection one-year post-HCT (5% vs. 44%; p = 0.004) and lower graft failure rates throughout the follow-up period. After a median follow-up of 5.2 years, the disease-free survival was 71% for the PC regimen. The PC preconditioning was associated with higher rates of full donor chimerism at 2-years post-HCT (0% vs. 43%; p = 0.02). Grade II-IV acute graft-versus-host disease (GVHD) rates were low; no patients developed moderate to severe chronic GVHD. There remain no cases of myeloid malignancy after PC. With the increased immunosuppression of PC, 23% of patients developed post-transplant lymphoproliferative disorder, 19% developed immune cytopenias, and 62% had viral reactivation. Summary Further study to determine an optimal nonmyeloablative haploidentical regimen for SCD patients with compromised organ function is imperative. Clinical trial registry ClinicalTrials.gov (NCT00977691, NCT03077542).